Side by side comparison of NOTA and DOTA for conjugation efficiency, gallium-68 labeling, and in vivo biodistribution of anti-mesothelin sdAb A1-His - Émilien N’Guessan; Sandrine Bacot; Florian Raes; Julien Leenhardt; Thibault Guenard; Laurent Dumas; Catherine Ghezzi; Daniel Fagret; Charlotte Lombardi; Alexis Broisat; Mitra Ahmadi (EJNMMI Radiopharmacy and Chemistry)
Abstract Background Mesothelin is a glycoprotein overexpressed in various cancers, with limited expression in healthy tissues. The single-domain antibody (sdAb, or nanobody) A1-His has previously successfully been validated in mice for the SPECT imaging of mesothelin positive tumors following radiolabeling with 99mTc. Our objective was to radiolabel this sdAb with 68Ga for PET imaging, exhibiting superior sensitivity and resolution than SPECT in clinical practice. To this aim, it was conjugated to NOTA chelator that is commonly employed for 68Ga labeling of antibody-derived tracers. In addition, the high affinity and specificity of A1-His sdAb position it as a promising candidate for theranostic applications. In anticipation of future radiolabeling with beta-emitting radionuclides, DOTA-conjugated A1-His was also evaluated. Given the high thermal stability of sdAbs, this DOTA-conjugated sdAb could potentially be implemented in future studies as a theranostic agent with beta-emitting radionuclides. Results A1-His was successfully conjugated to p-SCN-Bn-DOTA and p-SCN-Bn-NOTA under optimized conditions, achieving chelator-to-sdAb ratios of 1.8 and 1.3, respectively. NOTA-A1-His allowed rapid radiolabeling with 68Ga at room temperature, achieving high radiochemical purity (> 98%) within 5 min. Using DOTA, similar purity was obtained at 60 °C for 15 min. Both radiotracers demonstrated stability over 4 h in the radiolabeling medium and 2 h in human blood. However, some instability was observed in murine blood. Biodistribution and imaging studies in mice bearing mesothelin-expressing tumors showed specific tumor targeting for both tracers. Notably, [68Ga]Ga-DOTA-A1-His exhibited twofold lower kidney uptake compared to [68Ga]Ga-NOTA-A1-His, potentially enhancing imaging contrast and reducing renal radiation exposure. His-tag removal, further improves the biodistribution profile of the 2 tracers. Conclusions Both p-SCN-Bn-DOTA and p-SCN-Bn-NOTA chelators can be effectively conjugated to the A1 sdAb and radiolabeled with 68Ga, producing stable radiotracers with specific tumor-targeting capabilities. NOTA chelator offers advantages in rapid, room-temperature radiolabeling. However, DOTA would offer the advantage to be employed for theranostic approaches using β− emitters such as 177Lu or 161Tb. The lower kidney retention of DOTA-A1 also suggests that its dosimetry, a key factor in theranostic, would be more favorable.